Systematic review with meta‐analysis of over 90 000 patients. Does fast‐track review diagnose colorectal cancer earlier?. Issue 4 (8th July 2019) - Mozdiak, Ella; Weldeselassie, Yonas; McFarlane, Michael; Tabuso, Maria; Widlak, Monika M.; Dunlop, Amber; Tsertsvadze, Alexander; Arasaradnam, Ramesh P.
Summary: Background: National UK data on colorectal cancer (CRC) stage at diagnosis is incomplete. Site‐specific fast‐track (2‐week wait) cancer data are not collected directly by NHS England. Policy making based on these data alone can lead to inaccuracy. Aims: To review available data on key outcomes (cancer conversion rate and stage at diagnosis) for the UK's lower gastrointestinal 2‐week wait pathway. Methods: A comprehensive literature search was conducted between 2000 and 2017. Primary outcomes were cancer conversion rate and cancer stage at diagnosis. Results were expressed as proportions with 95% CIs. A random effects model was used for meta‐analysis; heterogeneity was assessed by I 2 . Results: Of 95 papers reviewed, 49 were included in analysis with a total study population of 93, 655. Cancer conversion rate was 7.7% (95% CI: 6.9‐8.5). The proportion presenting at Dukes A = 11.2% (95% CI 7.4‐15.6), B = 36.7% (95% CI 30.8‐42.8), C = 35.7% (95% CI: 30.8‐40.8) and D = 11.1% (95% CI 7.3‐15.5). No colonic pathology was diagnosed in 54.6% (95% CI: 46.2‐62.8). Conclusions: Only 7.7% of patients referred by the 2‐week wait pathway were found to have CRC. No beneficial effect on stage at diagnosis was found compared to non‐2‐week wait referral pathways. Over half of patients had no colonic pathology and detection of adenomas was very low. These results should prompt a reconsideration of the benefits of the 2‐week wait pathway in CRC diagnosis and outcomes, with more focus on strategies to improve patient selection.